The metabolic and renal effects of adrenaline and milrinone in patients with myocardial dysfunction after coronary artery bypass grafting - Heringlake, Matthias (BioMed Central, 2007)
INTRODUCTION: Myocardial dysfunction necessitating inotropic support is a typical complication after on-pump cardiac surgery. This prospective, randomized pilot study analyzes the metabolic and renal effects of the inotropes adrenaline and milrinone in patients needing inotropic support after coronary artery bypass grafting (CABG). METHODS: During an 18-month period, 251 patients were screened for low cardiac output upon intensive care unit (ICU) admission after elective, isolated CABG surgery. Patients presenting with a cardiac index (CI) of less than 2.2 liters/minute per square meter upon ICU admission – despite adequate mean arterial (titrated with noradrenaline or sodium nitroprusside) and filling pressures – were randomly assigned to 14-hour treatment with adrenaline (n = 7) or milrinone (n = 11) to achieve a CI of greater than 3.0 liters/minute per square meter. Twenty patients not needing inotropes served as controls. Hemodynamics, plasma lactate, pyruvate, glucose, acid-base status, insulin requirements, the urinary excretion of alpha-1-microglobuline, and creatinine clearance were determined during the treatment period, and cystatin-C levels were determined up to 48 hours after surgery (follow-up period). RESULTS: After two to four hours after ICU admission, the target CI was achieved in both intervention groups and maintained during the observation period. Plasma lactate, pyruvate, the lactate/pyruvate ratio, plasma glucose, and insulin doses were higher (p < 0.05) in the adrenaline-treated patients than during milrinone or control conditions. The urinary excretion of alpha-1-microglobuline was higher in the adrenaline than in the control group 6 to 14 hours after admission (p < 0.05). No between-group differences were observed in creatinine clearance, whereas plasma cystatin-C levels were significantly higher in the adrenaline than in the milrinone or the control group after 48 hours (p < 0.05). CONCLUSION: This suggests that the use of adrenaline for the treatment of postoperative myocardial dysfunction – in contrast to treatment with the PDE-III inhibitor milrinone – is associated with unwarranted metabolic and renal effects. Clinical trials registration: ClinicalTrials.gov NCT00446017.